[Fe–Fe] hydrogenase models: Iron(I)-carbonyl clusters coupled to alpha- and para-toluenethiolate ligands. (16th August 2016) - Haley, Adrian L.; Broadbent, Lauren N.; McDaniel, Lindsey S.; Heckman, Skye T.; Hinkle, Carlee H.; Gerasimchuk, Nikolay N.; Hershberger, John C.; Mebi, Charles A.
Graphical abstract: Two linkage isomers, [( μ 2 -( p -toluenethiolato))2 Fe2 (CO)6 ] (1 ) and [( μ 2 -( α -toluenethiolato))2 Fe2 (CO)6 ] (2 ) have been prepared in moderate yields. The composition and structure of the compounds were ascertained by elemental analysis, NMR spectroscopy and X-ray diffraction. Comparatively, compound1 electrochemical reduces proton to hydrogen at an overpotential 90 mV lower than compound2 . Abstract: Two linkage isomers composing of diironhexacarbonyl clusters coupled to α and p -toluenethiolate ligands have been usefully prepared in moderate yields. The composition of both compounds, [( μ 2 -( p -toluenethiolato))2 Fe2 (CO)6 ] (1 ) and [( μ 2 -( α -toluenethiolato))2 Fe2 (CO)6 ] (2 ), have been determined by elemental analysis and NMR spectroscopy. A tetrairondodecacarbonyl complex, [ μ 4 -S ( μ 2 -( α -toluenethiolato)Fe2 (CO)6 )2 ] (3 ), was isolated from the reaction mixture of2 . The molecular structures of2 and3 determined by X-ray diffraction are discussed. An exploration of the influence of the α- and p -toluenethiolate ligands on the electronic and electrochemical properties of the iron-carbonyl units have been accomplished using infrared spectroscopy, UV–Vis spectroscopy and cyclic voltammetry. In the presence of acetic acid, compounds1, 2 and3 catalyze the electrochemical generation of molecular hydrogen. The proton reduction overpotentials for compounds1 and2 were determined to be 0.76 V and 0.85 V versus Fc/Fc + respectively in acetonitrile as solvent. Comparatively, compound1 produces hydrogen at an overpotential 90 mV lower than compound2 .